2006
DOI: 10.1029/2006gl026234
|View full text |Cite
|
Sign up to set email alerts
|

Variability of natural hypoxia and methane in a coastal upwelling system: Oceanic physics or shelf biology?

Abstract: Emerging understanding of the variability of natural coastal hypoxia is divided between two main hypotheses: the biogeochemical oxygen demand linked to locally‐driven organic matter decay or to supply of low‐oxygen waters by physical processes. The precise role of either mechanism in triggering hypoxia has remained elusive. A combined methane and oxygen high resolution year‐long hourly data time series in a coastal upwelling system suggests that these systems may be responding to a complex interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
82
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 16 publications
8
82
0
Order By: Relevance
“…These effluxes were relatively high with respect to other coastal areas (see Bange, 1994) and comparable with CH 4 emissions from other coastal upwelling areas (Monteiro et al, 2006;Kock et al, 2008). CH 4 emission has been indirectly linked to high primary productivity, which favors CH 4 formation in sinking organic particles or in sediments (Owens et al, 1991;Sansone et al, 2001;Monteiro et al, 2006;Reeburgh, 2007).…”
Section: Methane Content In the Water Columnsupporting
confidence: 58%
See 3 more Smart Citations
“…These effluxes were relatively high with respect to other coastal areas (see Bange, 1994) and comparable with CH 4 emissions from other coastal upwelling areas (Monteiro et al, 2006;Kock et al, 2008). CH 4 emission has been indirectly linked to high primary productivity, which favors CH 4 formation in sinking organic particles or in sediments (Owens et al, 1991;Sansone et al, 2001;Monteiro et al, 2006;Reeburgh, 2007).…”
Section: Methane Content In the Water Columnsupporting
confidence: 58%
“…CH 4 emission has been indirectly linked to high primary productivity, which favors CH 4 formation in sinking organic particles or in sediments (Owens et al, 1991;Sansone et al, 2001;Monteiro et al, 2006;Reeburgh, 2007). But as shown in Table 2, the experimental work in this study indicated that part of the CH 4 contents seems to come from the surface waters and that such produced gas could be emitted to the atmosphere.…”
Section: Methane Content In the Water Columnmentioning
confidence: 63%
See 2 more Smart Citations
“…Naturally occurring hypoxia is found in bottom waters of silled basins and fjords with restricted circulation (e.g. Black Sea, Cariaco Basin, Kau Bay, Anderson and Devol, 1987;Middelburg et al, 1991), as a result of natural intrusions or upwelling of subsurface oxygen-depleted waters on shelf systems (northern Chile, Morales et al, 1999;northeast Pacific, Grantham et al, 2004;Costa Rica, Thamdrup et al, 1996; Namibian shelf, Monteiro et al, 2006Monteiro et al, , 2008Lavik et al, 2009;Indian shelf, Naqvi et al, 2000), or in coastal embayments such as estuaries from the heterotrophic status sustained by the delivery of terrestrial and riverine organic matter (Heip et al, 1995). Human influences on coastal hypoxia are multiple and can operate on local and regional scales (e.g.…”
Section: Introductionmentioning
confidence: 99%